2003
DOI: 10.1042/bss0700039
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and inducibility of TACE (tumour necrosis factor α-converting enzyme) revisited: the Ala-Val preference, and induced intrinsic activity

Abstract: Tumour necrosis factor α (TNFα)-converting enzyme (TACE/ADAM-17, where ADAM stands for a disintegrin and metalloproteinase) releases from the cell surface the extracellular domains of TNF and several other proteins. Previous studies have found that, while purified TACE preferentially cleaves peptides representing the processing sites in TNF and transforming growth factor α, the cellular enzyme nonetheless also sheds proteins with divergent cleavage sites very efficiently. More recent work, identifying the clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…In vitro, Nectin-4 cleavage by recombinant TACE results in the generation of a soluble form with a slightly higher molecular mass (data not shown). Differences in TACE cleavage position have been already reported in vitro using recombinant TACE and may explain this difference (29). The physiological inhibitor of TACE, TIMP-3, inhibits Nectin-4 cleavage.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro, Nectin-4 cleavage by recombinant TACE results in the generation of a soluble form with a slightly higher molecular mass (data not shown). Differences in TACE cleavage position have been already reported in vitro using recombinant TACE and may explain this difference (29). The physiological inhibitor of TACE, TIMP-3, inhibits Nectin-4 cleavage.…”
Section: Discussionmentioning
confidence: 96%
“…19 MPs (10 l) were suspended in 100 l of the final activity buffer (25 mmol/L Tris/HCl, pH 8.0, containing 2.5 mol/L ZnCl 2 ). Fluorogenic peptide I (substrate of MMP-1, -2, -7, -8, -9, -12, -13, -14, -15, and -16), peptide II (substrate of MMP-3 and -10) (R&D Systems), and peptide III were diluted in the activity buffer at the final concentration of 10 mol/L.…”
Section: Fluorogenic Assays Of Protease Activity Of Mpsmentioning
confidence: 99%
“…For example, it was observed that ADAM17 failed to cleave several full-length proteins in biochemical assays but was able to cleave peptides based on their cleavage sites (reviewed by Roy Black in Ref. 38). Among the full-length proteins that exhibited this behavior were pro-TGF␣ (35), L-selectin, p55 TNFR, and p75 TNFR (38), all validated physiological substrates of ADAM17.…”
mentioning
confidence: 99%
“…38). Among the full-length proteins that exhibited this behavior were pro-TGF␣ (35), L-selectin, p55 TNFR, and p75 TNFR (38), all validated physiological substrates of ADAM17. Moreover, the lack of suitable methodologies (long and expensive production process, sensitivity issues for HPLC-based methods, stability issues for fluorescamine labeling approach, etc.)…”
mentioning
confidence: 99%